DIVERSITY OF THE PUMPKIN COLLECTION AND ITS HEREDITARY POTENTIAL. RESULTS AND PROSPECTS OF BREEDING PRACTICE - A. G. Elatskova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Pumpkin is an important food, feed and medicinal crop. It is widely used by national cuisines in many countries and utilized as raw material for canning industry and in pharmacy to prepare drugs. The Kuban Experiment Station of VIR, where the collection of pumpkin genetic resources is maintained and regenerated for long-term storage in the genebank, conducts comprehensive research work to analyze the genetic diversity of pumpkin accessions and disclose the potential of its hereditary variation.Objective. The aim of this study was to screen various species from the global pumpkin collection and identify sources of traits valuable for breeders in order to develop promising cultivars and hybrids.Materials and methods. The pumpkin collection was studied and the breeding work was performed using the guidelines worked out by VIR’s scientists. The work included botanical description, study of variability and inheritance of traits, hybridization, inbreeding, mutagenesis, and different selection techniques (individual, group, individual/ family, and mass selection). In the first stages of the study, inbreeding was employed to select best plants from the collection in order to set up a trait-specific collection and incorporate its accessions into the hybridization process. Self-pollination was usedfor several years to obtain self-pollinated lines, sufficiently uniform in the selected trait. The hybrid progenies from crosses between parental forms were analyzed to throw light on the inheritance of major traits and their genetic control. The accessions were assessed for their earliness, productivity and quality. Evaluation of disease resistance was carried out in the field under natural infection pressure.Results and discussion. Targeted breeding efforts resulted in releasing cultivars of Cucurbita pepo L., C. maxima Duch. and C. moschata Duch. ex. Poir. having different maturation schedules and approved for cultivation in various regions of Russia: ‘Kustovaya oranzhevaya’, ‘Lechebnaya’, ‘Kustovaya zolotaya’, ‘Malyshka’, ‘Matreshka’, ‘Krasavitsa’, Zimnyaya sladkaya’, ‘Zhemchuzhina’, ‘Yantarnaya’ and ‘Mariya’. These cultivars are in demand among both agricultural producers and individual growers. New sources of valuable morphobiological and agronomic characters have been identified as useful for modern plant breeding trends: KL 625, ZhZM 692, L-180, L-193, KPL 168, KL 568 and KL 570. New bushy lines of C. maxima and C. moschata selected from cultivar and hybrid populations are now tested in an elite test nursery in order to submit the best of them to the State Variety Trials.